Implementasi Fungsi Preventif dan Represif dalam Patroli Kepolisian di Tingkat Polsek - Andasia, Junaidy; Moonti, Roy Marthen; Ahmad, Ibrahim (Lembaga Pengembangan Kinerja Dosen, 2025)
Police patrols at the Polsek level have a strategic role in maintaining public security and order through the implementation of preventive and repressive functions. The preventive function aims to prevent crime, while the repressive function focuses on law enforcement against violations. This research aims to analyze the implementation of the repressive function in Polsek patrol activities as a response to the dynamics of law violations in its jurisdiction. The type of research used is normative legal research with statutory and conceptual approaches. The results show that the effectiveness of repressive patrols is highly dependent on officer professionalism, technological support, and community synergy. In conclusion, the repressive function must be carried out proportionally, accountably, and humanistically. It is recommended that the police strengthen personnel capacity, evaluation systems, and data-based strategies to improve the effectiveness of law enforcement while building public trust in a sustainable manner.